Imperial Riding School - Winkles, Henry, 1801-1860 (engraver):::Creator::::::::::::; Batty, Robert, 1789-1848 (artist):::Contributor:::::::::::: (United Kingdom; Rodwell & Martin, printed by McQueen & Co.; London)
Engraving of the Imperial Riding School in Vienna